Massimo Pavarini e le città sicure. Patricia Victoria Perello’ intervista Massimo Pavarini. Universitad Nacional de Mar del Plata, Giugno 2013 - Bondi, Alessandro (Cultura giuridica e diritto vivente, 2016)
[Massimo Pavarini and the Urban Security] Urban security, perception of security, Government of public spaces, urban development, lived and consumed city, new citizenship, conflict dislocation, inclusion and exclusion policy, stereotypes, to be in politics: a criminologist life and his social commitment in one of the last interviews of Massimo Pavarini.